Correspondence between phenomenological and IBM-1 models of even isotopes of Yb - Okhunov, Abdurahim; Sharrad, Fadhil; Al-Sammarraie, Anwer Ahmed; Khandaker, Mayeen Uddin (IOP Publishing, 2015)
Energy levels and the reduced probability of E2– transitions for ytterbium isotopes with proton number Z = 70 and neutron numbers between 100 and 106 have been calculated through phenomenological (Ph.M.) and interacting boson (IBM-1) models. The predicted low-lying levels (energies, spins and parities) and the reduced probability for E2– transitions results are reasonably consistent with the available experimental data. The predicted low-lying levels (gr–, β1– and γ1– band) by produced in the Ph.M. are in good agreement with the experimental data comparison with those by IBM-1 for all nuclei of interest. In addition, the phenomenological model was successful in predicted the β2–, β3–, β4–, γ2– and 1+– band while it was a failure with IBM-1. Also, the 3+– band is predicted by the IBM-1 model for 172Yb and 174Yb nuclei. All calculations are compared with the available experimental data.